Testing possibilities: on negotiating writing practices in a ‘postdigital’ age (tools and methods). - Barnard, Josie (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2017)
The exponential growth of new media technologies presents opportunities and challenges for writers. Fast-paced change – featuring what can seem like perpetual updates of hardware and software – undermines the possibility of growing attached to particular tools and practices. Collaboration is key to social media and many of the new technologies, and not something that sits easily with the traditional image of the writer as someone working alone. This article considers how writers can negotiate the demands of a ‘postdigital age’. Adopting a teacher-practitioner stance, it proposes that the remediation of a writer’s own practice is key. As well as considering how a writer can work to remediate his or her own practice, whereby – as new challenges and opportunities arise – a writer looks to existing skills and prior experience and adapts or applies them in new contexts as part of a process of, in effect, collaborating with him or herself, this article begins to explore whether such remediation can be taught. An aim is to reach a new theoretical position on how individuals can approach the creative potential of writing in the twenty-first century and more effectively embrace existing and emerging opportunities provided by interactive digital technologies.